Ionized-air-treated curaua fibers as reinforcement for phenolic matrices - Trindade, Wanderson Goncalves; Faulstich de Paiva, Jane Maria; Leão, Alcides Lopes [UNESP]; Frollini, Elisabete (Wiley-v C H Verlag Gmbh, 2008)
Curaua fibers were treated with ionized air to improve the fiber/phenolic matrix adhesion.The treatment with ionized air did not change the thermal stability of the fibers. The impact strength increased with increase in the fiber treatment time. SEM micrographs of the fibers showed that the ionized air treatment led to separation of the fiber bundles. Treatment for 12 h also caused a partial degradation of the fibers, which prompted the matrix to transfer the load to a poorer reinforcing agent during impact, thereby decreasing the impact strength of the related composite. The composites reinforced with fibers treated with ionized air absorbed less water than those reinforced with untreated fibers.
Keywords: curaua fibers; impact strength; ionized air; thermal stability; thermoset phenolic matrix; water absorption